2006
DOI: 10.1016/j.jana.2006.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Mobility in Relation to Chronic Venous Insufficiency in HIV-Positive Persons With and Without a History of Injection Drug Use

Abstract: The purpose of this study was to examine ankle mobility in relation to chronic venous insufficiency (CVI) in HIV-positive persons with and without a history of injection drug use (IDU) and to examine the extent to which peripheral neuropathy further reduced ankle mobility. A cross-sectional, stratified design with quota sampling was used to recruit 27 persons with no history of IDU and 46 with a history of IDU from an infectious diseases clinic. Goniometric measurements of forefoot inversion-eversion and dorsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Chronic wounds also have a social impact. The chronic pain, reduced mobility, malodor and stigma can marginalize these individuals and may make it difficult to maintain financial security and social support (Palfreyman et al, 2007; Pieper et al, 2007; Pieper, Templin, Goldberg, DiNardo, & Wells, 2013; Pieper, Templin, & Ebright, 2006). The prevalence of and risk factors for chronic ulcers in the IDU population has not been well studied or evaluated concurrently with risk factors for abscesses in this population.…”
mentioning
confidence: 99%
“…Chronic wounds also have a social impact. The chronic pain, reduced mobility, malodor and stigma can marginalize these individuals and may make it difficult to maintain financial security and social support (Palfreyman et al, 2007; Pieper et al, 2007; Pieper, Templin, Goldberg, DiNardo, & Wells, 2013; Pieper, Templin, & Ebright, 2006). The prevalence of and risk factors for chronic ulcers in the IDU population has not been well studied or evaluated concurrently with risk factors for abscesses in this population.…”
mentioning
confidence: 99%
“…In a study of human immunodeficiency virus-positive persons, we found that injection drug users had less ankle plantar and dorsiflexion and inversion-eversion than those who did not inject drugs. 4 A causal model supported the hypothesis of ankle mobility as a mediator of the effect of IDU on CVD. Significant impairment of quality of life occurred with leg pain causing increased functional impairment with worsening CVD; stair climbing and walking were also adversely affected.…”
Section: Chronic Venous Disease and Injection Drug Usementioning
confidence: 66%
“…27 Thus, severity of CVD was associated with reduced ankle joint motion. Using goniometry, one can measure joint angles including dorsiflexion (upward foot movement), plantar flexion (downward foot movement), inversion (inward foot movement), and eversion (outward foot movement).…”
Section: Ankle Mobilitymentioning
confidence: 99%